PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA SERTA DAMPAKNYA TERHADAP PEREKONOMIAN WARGA DI DESA KOMBANG KABUPATEN SUMENEP - Farihah, Durrotul Farihah; Firman, Firman; Arie Wahyu Prananta, Arie Wahyu Prananta; Raja Dasion, Agustinus Gergorius (Jurnal Sosial-Politika, 2023)
The research aims to determine participation in the development of tourist villages and their impact on the economy of residents in Kombang village, Sumenep district. Ecotourism industry and the creative economy are encouraged to be able to have an impact in the form of income distribution, especially fishermen in Gili Labak, Sumenep Regency. The development of the ecotourism and tourism culture concept in an industry based on online traveling services using Telegram is actually an interesting development in regions that focus on tourism services based on the wishes of tourist visitors. Problems, serious problems and dilemmas in tourism management and development, dilemmatic problems faced in a choice of continuing to run a tourism business to increase income and meet the economic needs of the local population as well as environmental sustainability issues in places where the tourism sector is the sector that is affected first and its recovery the very last. It is hoped that this research will provide a solution to this dilemma. The concept of ecotourism development is oriented towards environmental education and the ecosystem concept and is integrated with the existence of social media in the form of One Stop Service Traveling (OSST) by both telegram groups as a means of promotion and presentation of statistically clear information on the factual conditions of tourist destinations at any time in providing reliable information services. professionals to restore the much needed and important tourism sector. Weaknesses and Obstacles faced: So dynamic and complex social problems arise from a conceptual justification of the 5 things above when considered as a basis for determining optimization of service quality that will support the sustainability of sustainable ecotourism development. On the other hand, those who use Telegram groups are prone to irresponsible advertising intruders, whether it be hoax advertisements or pornographic advertisements. The number of tourists or travelers visiting during the current Covid-19 pandemic, which is limited to the number of visitors per day, will have an impact on increasing residents' income, which will take a long and slow time. There is a need for an effective marketing strategy and outreach with the traveler community, both on a national and international scale.